Дослідження на базі перших принципів впливу концентрації на електронні та вібраційні влас¬тивості бор-алюмофосфідного сплаву з вурцоїдною наноструктурою - Fayyadh, H.A. (Publishing house "Academperiodika", 2023)
The vibrational and electronic properties of the binary wurtzoids Al7P7 and B7P7 and the ternary one BxAl7-xP7 have been investigated by the use of the approximation of the Density Functional Theory (DFT). By varying the concentration x, we carried out the calculations and various simulations of the bond lengths, energy gap, density of states, force constants, reduced masses, and infrared and Raman spectra. The geometric nanostructure of BxAl7-xP7 wurtzoid has been analyzed using the Gauss view 05 program. As the concentration of B increases, the energy gap widens, indicating that the estimations are consistent with the experimental longitudinal optical measurements. We utilize the theoretical ab initio technique to mimic the properties and nanostructures of BxAl7-xP7 wurtzoid using DFT B3LYP with the 6-311-G** basis sets and the GGA calculations with all electrons.